Implementation of Article 6c of the Minister of Transportation Regulation Number 12 of 2019 concerning Protection of the Safety of Motorcycle Users against Motorists Who Smoking in East Banjarmasin District - Astiana; Ergina Faralita (Indonesian Journal of Islamic Jurisprudence, Economic and Legal Theory, 2023)
ABSTRACT Smoking is a way of life for some people, from parents, teenagers, men, women and even children. Smoking is now an activity that is often found in various places, even on the highway, drivers and drivers are very often found smoking while driving. Minister of Transportation Regulation No. 12 of 2019, which contains Article 6C which prohibits motorists from smoking while driving, is issued to maintain public safety and minimize the impact of smoking drivers. However, in its implementation there are still many encountered from both the service, police and the community, lack of communication and lack of coordination and public awareness. The purpose of this research is to find out how the implementation of Permenhub No. 12 of 2019 concerning the protection of the safety of motorbike users who are used for the benefit of society. And to identify obstacles in the implementation. This research is an empirical legal research with a sociological legal approach, researchers conducted observations and interviews with 2 agencies, namely the Banjarmasin City Transportation Service and the Banjarmasin Police Traffic Unit as well as 20 driver informants who were in research locations in East Banjarmasin District. This study found that the implementation of the Minister of Transportation Regulations had not been fully implemented properly, as seen from the number of motorists who smoke while driving which is the object of the author's research. And there are 5 obstacles in the implementation of this regulation, namely communication, resources, disposition, public awareness about the law and no strict sanctions from the police against violators. Keywords: Implementation, Motorists, Smoking, Banjarmasin ABSTRAK Merokok merupakan gaya hidup bagi sebagian orang, mulai dari orang tua, remaja, pria, wanita bahkan anak-anak. Merokok kini menjadi kegiatan yang sering dijumpai di berbagai tempat, bahkan di jalan raya pun sangat sering dijumpai pengemudi dan pengendara yang merokok sambil berkendara. Peraturan Menteri Perhubungan No. 12 Tahun 2019 yang memuat Pasal 6C yang melarang pengendara kendaraan bermotor untuk merokok saat berkendara dikeluarkan untuk menjaga keselamatan masyarakat dan meminimalisir dampak dari pengemudi yang merokok. Namun dalam pelaksanaannya masih banyak ditemui baik dari pihak dinas, kepolisian maupun masyarakat, kurangnya komunikasi dan kurangnya koordinasi serta kesadaran masyarakat. Tujuan dari penelitian ini adalah untuk mengetahui bagaimana implementasi Permenhub No. 12 Tahun 2019 tentang perlindungan keselamatan pengguna sepeda motor yang digunakan untuk kepentingan masyarakat. Serta untuk mengetahui hambatan-hambatan dalam pelaksanaannya. Penelitian ini merupakan penelitian hukum empiris dengan pendekatan hukum sosiologis, peneliti melakukan observasi dan wawancara kepada 2 instansi yaitu Dinas Perhubungan Kota Banjarmasin dan Satlantas Polresta Banjarmasin serta 20 orang informan pengemudi yang berada di lokasi penelitian di Kecamatan Banjarmasin Timur. Penelitian ini menemukan bahwa implementasi Peraturan Menteri Perhubungan belum sepenuhnya terlaksana dengan baik, terlihat dari masih banyaknya pengendara yang merokok sambil berkendara yang menjadi objek penelitian penulis. Dan terdapat 5 hambatan dalam implementasi peraturan ini yaitu komunikasi, sumber daya, disposisi, kesadaran masyarakat tentang hukum dan tidak adanya sanksi yang tegas dari pihak kepolisian terhadap para pelanggar. Kata kunci: Implementasi, Pengendara Kendaraan Bermotor, Merokok, Banjarmasin